The effectiveness of riparian buffer zones for protecting waterways during harvest in the Pipiwai forest in Northland, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Science in Natural Resource Management, Massey University, Palmerston North, New Zealand - Hanmore, Ian (Massey University, 2007)
The harvest of plantation forests has the potential to cause significant negative impacts on the waterways that flow through them. It has been proposed that to mitigate any such impacts waterways should be protected by undisturbed riparian buffer zones (RBZ). As such, this research has been conducted to investigate if RBZs protect plantation waterways during harvest. To do this a case study was carried out in the Pipiwai forest, one of Carter Holt Harvey Forests (CHHF) Northland plantations. In the investigation, 15 first order streams were sampled using an extended version of NIWA's stream health monitoring and assessment kit (SHMAK). The samples were taken from three different stream treatments, those harvested with undisturbed buffers, harvested with no buffers (clearcut) and standing mature pine forest. Each site had the quality of its aquatic and riparian habitats and invertebrate communities assessed via the SHMAK, which presented a rating for each streams health. Statistical analysis was also carried out to determine if any differences in the results were significant or simply an expression of the variation that could be expected in a single population. The management of the plantation was also investigated. CHHF managers were interviewed to determine the activities that could have impacted on the forest's waterways. The results showed that clearcut streams had degraded riparian and aquatic habitats through the loss of vegetation, exposed and eroding soil, and increased streambed sedimentation. This degradation was reflected in the invertebrate communities which were dominated by high numbers of pollutant tolerant species such as mollusks and midges. Buffered waterways, however, had no such degradation and their invertebrate communities had high numbers of pristine requiring invertebrates such as mayflies. Statistical analysis showed that the habitat and invertebrate scores of the clearcut sites were significantly lower than the buffered and pine sites, and it also showed there was no significant difference between the buffered sites and the mature pine sites. The results also showed that the management of the Pipiwai plantation was conducted to industry and council standards, but that this was insufficient to prevent the degradation of the waterways in the clearcut catchments. The two main conclusions of this research were that RBZs in the Pipiwai forest protected waterways from degradation during plantation harvest and maintained them in a state similar to that of standing mature pine forest, and that management practices and regulations in use at the time of harvest, though within industry and government standards, were unable to prevent waterway degradation and achieve results equal to those of the RBZs.
Keywords: New Zealand -- Northland; Buffer zones (Ecosystem management); Riparian ecology; Clearcutting -- Environmental aspects